Ranolazine Inhibits Pyroptosis via Regulation of miR-135b in the Treatment of Diabetic Cardiac Fibrosis - Ren, Long; Chen, Xi; Nie, Binyang; Qu, Huan; Ju, Jiaming; Bai, Yunlong (Frontiers in Molecular Biosciences, 2022)
Diabetic cardiomyopathy (DCM) is a major cardiovascular complication of diabetes mellitus (DM), and cardiac fibrosis is a characteristic pathological manifestation of DCM. DCM can be exacerbated by pyroptosis, and pyroptosis is a potential target of microRNAs (miRNAs). miR-135b is involved in delaying the progression of numerous cardiovascular diseases, Nonetheless, the role of miR-135b in diabetic cardiac fibrosis is unclear. Ranolazine is a piperazine derivative and is effective for the treatment of cardiovascular disease. The purpose of the study was to elucidate the mechanism of ranolazine in diabetic cardiac fibrosis and to investigate the role of miR-135b in this process. Functional and structural changes in the rat heart were examined by echocardiography, hematoxylin-eosin (H&E) and Masson staining. Immunohistochemistry was used to assess the expression of caspase-1, interleukin-1β (IL-1β), gasdermin D (GSDMD), transforming growth factor-β1 (TGF-β1), collagen I and collagen III in the rat left ventricle. Western blot and immunofluorescence were used to detect the protein expression of caspase-1, IL-1β, GSDMD, TGF-β1, collagen I and collagen III proteins, and the mRNA levels were determined using fluorescent quantitative PCR. Ranolazine reduced pyroptosis and inhibited collagen deposition, improving cardiac function in rats. Ranolazine increased miR-135b expression in high glucose-treated myocardial fibroblasts, and miR-135b directly bound to caspase-1. Interference with miR-135b reduced the effects of ranolazine on pyroptosis and collagen deposition. Ranolazine treatment of diabetic cardiac fibrosis inhibited pyroptosis and collagen deposition by upregulating miR-135b. Our study provided a solid theoretical basis for understanding the pathogenesis of diabetic cardiac fibrosis and the clinical use of ranolazine in the treatment of DCM.